2015
DOI: 10.1068/a130012p
|View full text |Cite
|
Sign up to set email alerts
|

In the Family Way: Bringing a Mother-Daughter (Matrilineal) Perspective to Retail Innovation and Consumer Culture

Abstract: Davies A and Fitchett, J.A. (2015) "In the family way: bringing a mother-daughter (matrilineal) perspective to retail innovation and consumer culture" Environment and Planning A, 47 (3): [727][728][729][730][731][732][733][734][735][736][737][738][739][740][741][742][743] In the family way: bringing a mother-daughter (matrilineal) perspective to retail innovation and consumer cultureHere we apply the multi-level narrative approach of critical oral history to develop intergenerational narratives that show how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 81 publications
(115 reference statements)
0
9
0
Order By: Relevance
“…Marketing has had a strong interest in intergenerational transmission of consumer behaviours, attitudes and values, which are seen as vital in long-term brand value and consumer socialisation (Davies et al, 2013). However, a cutting-edge research drawing on three generations of British women revealed how consumer behaviour within the family is shaped by intergenerational continuities and discontinuities (Davies and Fitchett, 2015). The research demonstrated how family identities are formed through negotiated efforts, everyday consumption practices and retail innovations (Davies and Fitchett, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marketing has had a strong interest in intergenerational transmission of consumer behaviours, attitudes and values, which are seen as vital in long-term brand value and consumer socialisation (Davies et al, 2013). However, a cutting-edge research drawing on three generations of British women revealed how consumer behaviour within the family is shaped by intergenerational continuities and discontinuities (Davies and Fitchett, 2015). The research demonstrated how family identities are formed through negotiated efforts, everyday consumption practices and retail innovations (Davies and Fitchett, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…However, a cutting-edge research drawing on three generations of British women revealed how consumer behaviour within the family is shaped by intergenerational continuities and discontinuities (Davies and Fitchett, 2015). The research demonstrated how family identities are formed through negotiated efforts, everyday consumption practices and retail innovations (Davies and Fitchett, 2015). Considering the rapid and dramatic changes taking place in the Irish environment, research into the intergenerational dynamics that are shaping consumer behaviour can provide useful insights to academics and marketing practitioners alike.…”
Section: Resultsmentioning
confidence: 99%
“…Epp and Price (2008) consider families as comprising bundles of relational identities, which moderate the socialisation of central family practices. These relational, interactionist notions of the family have allowed consumer researchers to illuminate sibling relations (Kerrane et al, 2015), intergenerational consumption (Karanika and Hogg, 2016;Davies and Fitchett, 2015) and senior families (Huff and Cotte, 2016). Researchers have also focussed on different formulations of family identity and how it is negotiated across cultural settings (Edirisingha et al, 2015;Wong and Hogg, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Intergenerational storytelling implies at least three generations: grandparents, parents, and their children (Davies & Fitchett, 2015). Each generation, according to Jürgen Reulecke, "makes its decisions based on the rich experience it is carrying forward and that which it has accumulated itself," provoking stimulating changes in how stories are told (Reulecke, 2008, p. 124).…”
Section: Family Storytellingmentioning
confidence: 99%
“…On the one hand, mothers transmit to their daughters various types of canonical stories that provide a sense of the structures of sex/gender subordination. On the other, daughters internalize them as their own and often transfer them to their own daughters (Davies & Fitchett, 2015). As such, daughters are frequently influenced by their mothers stories, "either mimicking or by actively resisting them" (Davies & Fitchett, 2015, p. 729-30) within a generation system.…”
Section: Mother and Daughter Storytellingmentioning
confidence: 99%